The haplotype M2 of the ANXA5 gene is not associated with antitrophoblast antibodies - Rogenhofer, Nina (Springer US, 2013)
PURPOSE: The M2 haplotype in ANXA5 as well as antitrophoblast antibodies predispose to recurrent pregnancy loss (RPL). Since M2/ANXA5 can be a factor for development of antiphospholipid antibodies (aPL), this study aimed to trace a possible association of M2 with antitrophoblast antibodies. METHODS: One hundred patients with two or more consecutive, idiopathic RPLs were divided in two subgroups, JEG-3(+) (n = 42) and JEG-3(−) (n = 58), according to the anti-JEG-3 reactivity measured in subjects’ sera. Both subgroups were genotyped for ANXA5 promoter haplotypes and genetic frequencies were compared to available fertile and control populations, as well as within the subgroups. RESULTS: M2/ANXA5 was generally enriched in the JEG-3 screened cohort of RPL patients in comparison to fertile and population controls. Despite the relatively higher abundance of the haplotype in the JEG-3(−) sample as compared to JEG-3(+) patients and in the JEG-3(−) primary RPL subset in particular, compared to the rest of patients, there was no statistically significant difference between both, JEG-3(−) and JEG-3(+) subgroups. CONCLUSION: It appears that the haplotype M2/ANXA5 is not associated with the presence of anti-trophoblast antibodies. Our finding indicates that anti-trophoblast antibodies are a class of molecules that differ from aPL and from anti-b2-GPI antibodies, apparently not directed to same or similar epitopes that aPL and anti-b2-GPI would recognize.